2020
DOI: 10.5267/j.ccl.2019.8.002
|View full text |Cite
|
Sign up to set email alerts
|

A study to use activated sludge anaerobic combining aerobic for treatment of high salt seafood processing wastewater

Abstract: Seafood processing operations generate a high strength wastewater, which contain organic pollutants in soluble, colloidal, particulate form and salt content, up to 30g NaCl/L. This research aimed to study the effect of salt (NaCl) concentration on the treatment efficiency of seafood processing wastewater by the use of a laboratory-scale bioreactor, which is operated in anaerobic combining aerobic system with concentration salt different from 0-5%. The results showed that the wastewater from seafood processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Salinity increases are usually linked to a worsening in the system performance (Pham and Nguyen, 2020;Cristóvão et al, 2016). However, the driving mechanisms of this common behaviour are generally unknown, and the effect of salinity over eukaryotic populations, which play a key role in wastewater treatment, has been rarely studied.…”
Section: Roles Of the Core Phylum-like Taxa In Wwtpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Salinity increases are usually linked to a worsening in the system performance (Pham and Nguyen, 2020;Cristóvão et al, 2016). However, the driving mechanisms of this common behaviour are generally unknown, and the effect of salinity over eukaryotic populations, which play a key role in wastewater treatment, has been rarely studied.…”
Section: Roles Of the Core Phylum-like Taxa In Wwtpsmentioning
confidence: 99%
“…In this sense, different mechanisms to protect eukaryotic cells of the negative effect of NaCl have been developed by eukaryotes (Fuentes et al, 2016;Harding and Simpson, 2018;Vashishtha and Meghwanshi, 2018). Besides, Pham and Nguyen (2020) previously reported that the efficiency of CAS systems was significantly affected under NaCl contents >3% due to cell lysis. The results presented here indicate that a broader eukaryotic diversity could reduce the negative effect of NaCl and promote the colonization of the different ecological niches.…”
Section: Effect Of Nacl On Eukaryotic Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent environmental damage, fish-processing wastewater requires treatment before disposal. The normal performance of treatment processes of fish wastewater within the wastewater treatment plants includes physicochemical treatments as primary units for the removal of oils and the particulate matter followed by biological reactors (oxidation basin) for the removal of dissolved organic materials with the aid of activated sludge [4]. The conventional treatment using activated sludge systems are widely employed to treat both industrial and urban wastewater due to their adaptability and flexible operations.…”
Section: Introductionmentioning
confidence: 99%
“…There was a gradual increase in the microbial concentration over the 7-day period. The wastewater from rice paper manufacturing facility is rich in carbon sources, and the aerobic microorganisms can thrive in the aerotank because of the oxygen supplied from the aerated system [20,21,22]. In their study, Fan et al [20] reported that, when high levels of total phosphorus (TP), suspended solids (SS), and chemical oxygen demand (COD) were present in the wastewater, the MLSS was positively correlated, while the in uent ammonia levels were negatively associated with the MLSS.…”
mentioning
confidence: 99%